Density functional theory based-study of 5-fluorouracil adsorption on Betha-cristobalite (111) hydroxylated surface: the importance of H-bonding interactions - Díaz Compañy, Andrés Carlos Daniel (2015)
Silica-based mesoporous materials have been recently proposed as an efficient support for the controlled release of a popular anticancer drug, 5-fluorouracil (5-FU). Although the relevance of this topic, the atomistic details about the specific surface-drug interactions and the energy of adsorption are almost unknown. In this work, theoretical calculations using the Vienna Ab-initio Simulation Package (VASP) applying Grimme’s—D2 correction were performed to elucidate the drug–silica interactions and the host properties that control 5-FU drug adsorption on -cristobalite (1 1 1) hydroxylated surface. This study shows that hydrogen bonding, electron exchange, and dispersion forces are mainly involved to perform the 5-FU adsorption onto silica. This phenomenon, revealed by favorable energies, results in optimum four adsorption geometries that can be adopted for 5-FU on the hydroxylated silica surface. Silanols are weakening in response to the molecule approach and establish H-bonds with polar groups of 5-FU drug. The final geometry of 5-FU adopted on hydroxylated silica surface is the results of H-bonding interactions which stabilize and fix the molecule to the surface and dispersion forces which approach it toward silica (1 1 1) plane. The level of hydroxylation of the SiO2 (1 1 1) surface is reflected by the elevated number of hydrogen bonds that play a significant role in the adsorption mechanisms.